Drug Delivery: Ultrasound‐Triggered Regulation of Blood Glucose Levels Using Injectable Nano‐Network (Adv. Healthcare Mater. 6/2014). Issue 6 (June 2014) - Di, Jin; Price, Jennifer; Gu, Xiao; Jiang, Xiaoning; Jing, Yun; Gu, Zhen
<x xml:space="preserve">Abstract</x> On page 811, Y. Jing, Z. Gu and co‐workers present the integration of an injectable nano‐network with a focused ultrasound system (FUS) which can remotely regulate insulin release both in vitro and in vivo. Serving as a synthetic insulin reservoir, the nano‐network consisting of adhesive biodegradable nanoparticles promotes insulin release upon FUS triggers in a pulsatile, remote and non‐invasive control manner. Image courtesy of Dwayne Martin. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>